If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -8(-8x) = -6x + -22 Remove parenthesis around (-8x) -8 * -8x = -6x + -22 Multiply -8 * -8 64x = -6x + -22 Reorder the terms: 64x = -22 + -6x Solving 64x = -22 + -6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6x' to each side of the equation. 64x + 6x = -22 + -6x + 6x Combine like terms: 64x + 6x = 70x 70x = -22 + -6x + 6x Combine like terms: -6x + 6x = 0 70x = -22 + 0 70x = -22 Divide each side by '70'. x = -0.3142857143 Simplifying x = -0.3142857143
| 3(5x-10)=9 | | -8(-8x-6)=-6x-23 | | x-4+5=23 | | f(x)=10+x^2-5x^3 | | 3c+4=12+c | | 0.25x=.48 | | 0.25x=48 | | 6x+5y+4x-3y= | | 2(20+0)=-2+2x | | g^2*g^3= | | 5x+5(20-0)=10x | | -m-8=7 | | -x-2(4+0)=1-2x+10 | | 23=3m-7 | | y/-7=13 | | 37/8-10/3 | | 3/4-5/6 | | 2/5-3/7 | | 1.2/9+2.5 | | 3+2(p-6)=6p+33 | | x/-6=5 | | 1/3+1/2 | | (10/3)/(1/3) | | x+3/5=-27/5 | | 10/3/1/3 | | 2x-3(3+0)=10-x | | 17/7/4 | | 7/15/21/10 | | 9x+24=5x+4 | | 7+9k=25 | | 1/2/3/8 | | 2(x-1)=5/2 |